Pesticides: classifications, exposure and risks to human health - Castagna Cezimbra Weis, Grazielle; de Oliveira Alves, Audrei; Assmann, Charles Elias; da Silva Rosa Bonadiman, Beatriz; Costabeber, Ijoni Hilda (Archives in Biosciences & Health, 2019)
Pesticides are used in the control and prevention of pests, improving the productivity and the quality of agricultural production. The adoption of the Brazilian agricultural model, which uses pesticides on a large scale and indiscriminately, has been worrying public authorities about their impacts on human health and environmental sustainability. Thus, studies that contribute to a better understanding of agrochemicals and their effects on ecosystems and human health are timely. The aim was to investigate the history of the production and use of pesticides, their classifications, sources of exposure and their risks to human health. The research was carried out through literature review in databases to verify scientific information about the history of pesticides, structural and toxicological classifications, sources of exposure and their risks to human health. The use of pesticides dates back many years. During the nineteenth century until the mid-twentieth century, some chemicals nowadays used was pesticides were used for public health or for war purposes. About the classification of pesticides, due to the different biological targets, the agrochemicals market is segmented into different action targets (herbicides, fungicides and insecticides). Pesticides can be classified as contact, ingestion or systemic according to the mode of action. As for the chemical structure, the main classes of pesticides are organochlorines, organophosphates, pyrethroids and carbamates. The toxicity of pesticides ranges from low toxic to extremely toxic. Exposure to pesticides can occur directly through occupational exposure, or indirectly, through environmental exposure and food. The impacts on human health are divided into acute and chronic form. The prolonged human exposure to pesticides may result in neurological, reproductive, teratogenic and immunological disorders. The results presented in this literature review contribute to a better understanding of agrochemicals and their effects on human health.